Effects of topical application of mixtures of Morinda citrifolia L., Melastoma malabathricum L., and Lawsonia inermis L. ethanolic extracts on excision wound in sprague dawley rats - Al-Saeed, Ali Khairullah Zahi (2015)
The eligibility of attempting to repair excision wounds has long-term been appreciated since the last century, at least in the sensation of providing a spotless wound, avoiding formalization of purulent and pulverization as well as to boost a granulation and reepithelisation. It has been a particular vision in medical practice as excision wound denatures cellular protein, inhibits cellular metabolism hence secondary interference of local vascular supply. Therefore, the present study was designed to investigate the effects of the mixture of ethanolic extracts of Morinda citrifolia fruits, Melastoma malabathricum leaves and Lawsonia inermis leaves on the excision wound healing as these natural herbs have been traditionally used in excision wound treatment. Prior to wound healing experiment, the dermal toxicity levels of each herbal extract were determined via dermal toxicity experiments using the Organization for Economic Cooperation and Development (OECD) standard guidelines. Results showed that the lethal dose 50 (LD50) of each herb was more than 5000 mg/kg body weight, while the no observed adverse effect level (NOAEL) for each extract was more than 2000 mg/kg body weight. Based on the dermal toxicity results, mixtures of the herbal extracts at 0.5% and 1% were selected for treatment in the wound healing study. An area of uniform wound 2 cm in diameter was inflicted on 120 adult male Sprague Dawley weighing between 250-350 g. The animals were divided into five groups with six animals in each group, representing a control and experimental groups. Mixture of the herbs at 0.5%, mixture of the herbs at 1%, silver sulphadiazine as a standard treatment and paraffin were applied once daily, except in the control group where wounds were left without any topical treatment.The rats were closely monitored to assess any changes. The rats were euthanized at 4, 8, 12 and 21 days post wounding. The macroscopic appearances of excision wounds were evaluated and recorded. The percentages of wound contraction, wound size and wound epithelisation were measured and analyzed. In addition, histopathological examination of the skin was also performed qualitatively and quantitatively using haematoxylin and eosin (H&E), van Gieson and immunohistochemistry staining methods. Results obtained from this study revealed that mixture of three herbs at 0.5% showed advanced effects to decrease the period of wound healing process, wound contraction and wound size as compared to the other experimental groups. Quantitative evaluation of the number of inflammatory cells (polymorphonuclear cells and macrophages) from day 4 to day 21 in wounds treated with mixture of herbs at 0.5% demonstrated significant (p > 0.05) decrease in number of inflammatory cells from day 4 to day 21, while the number of proliferative cells (fibroblasts) increased from day 8 to day 21. Mixture of the herbs at 0.5% also showed potential to preserve viable dermal tissues and induce a well-formed of angiogenesis with better organisation as compared to the other experimental groups. On the other hand, the re-epithelisation and level of collagen formation was increased gradually in group that received mixture of herbs at 0.5% compared to the other groups. Qualitative and quantitative evaluation of the expression of vascular endothelial growth factor (VEGF), transforming growth factor alpha (TGF α) and transforming growth factor beta (TGF β) proteins in wounds treated with mixture of herbs at 0.5% and 1% recorded gradual rise in the expression of these three growth factors in wound area. In conclusion, the present study showed that mixture of the three herbs at 0.5% had the most superior treatment agent for excision wounds fallowed by mixture of the herbs at 1% in relation to the macroscopic and histopathological evaluation.